On the Incidence of Civil War in Africa. - Collier, P; Hoeffler, A (SAGE Publications, 2002)
An econometric model of civil war is applied to the analysis of conflict in sub-Saharan Africa. Results show that Africa has had a similar incidence of civil conflict to other developing regions, and, with minor exceptions, its conflicts are consistent with the global pattern of behavior. However, the structure of risk differs considerably from other regions. Africa's economic characteristics have made it more vulnerable to conflict, but this has been offset by social characteristics that make its societies atypically safe. The contrasting trends of conflict are analyzed: rising in Africa and declining in other regions. Results show that these trends are predicted by the model. Africa's rising trend of conflict is due to its atypically poor economic performance.